Physical Performance Is Associated with Executive Functioning in Older African American Women - Brooke C. Schneider; Peter A. Lichtenberg (Journal of Aging Research)
An older adult's ability to perform physical tasks is predictive of disability onset and is associated with declines in cognition. Risk factors for physical performance declines among African Americans, a group with the highest rates of disability, remain understudied. This study sought to identify demographic, health, and cognitive factors associated with lower-extremity physical performance in a sample of 106 African American women ages 56 to 91. After controlling for global cognitive functioning (Mini Mental State Exam), physical performance was associated with executive functioning (Stroop Color/Word), but not visuospatial construction (WASI Block Design) or processing speed (Trail Making Test, Part A). Executive functioning remained associated with physical performance after entry of demographic variables, exercise, depression, disease burden, and body mass index (BMI). Age, and BMI were also significant in this model. Executive functioning, age and BMI are associated with lower-extremity physical performance among older African American women.